The role of mediastinoscopy in the diagnosis of thoracic disease: 107-case analysis - Hasan Oğuz Kapicibaşi (Medicinski glasnik, 2019)
Aim: To evaluate the efficacy, safety and feasibility of mediastinoscopy in 107 cases with mediastinal lesions that could not be diagnosed histopathologically with other methods. Methods: A total of 107 cases (73 males, 34 females; mean age 57.4, range 30-88 years) with mediastinal lymphadenopathy, who underwent mediastinoscopy between 12 September 2012 and 29 November 2018 were examined retrospectively. The cases were evaluated in terms of age, gender, complaint, operation time, histopathological diagnosis, postoperative morbidity and mortality parameters. Results: Upon histopathological examination 32 (30%) patients were diagnosed with lung cancer metastasis (N2 stage), which was the most common diagnosis. With this diagnosis unnecessary thoracotomy was prevented. In patients with pathological lymphadenopathy found by imaging histopathological results were examined to evaluate the presence of N2 stage. In 25 (23.5%) cases biopsy results were reported as reactive lymph nodes. In addition, 23 (21.4%) patients had sarcoidosis, 16 (15%) had tuberculosis lymphadenitis, seven (6.5%) had lymphoma, one of each (0.9%) had benign epithelial cyst (0.9%), malign epithelial tumour (invasive ductal carcinoma of breast), chronic lymphocytic leukaemia (CLL), and adenocarcinoma metastasis (renal cell cancer). Conclusion: When other non-invasive procedures are ineffective, mediastinoscopy is an efficient diagnostic method with high diagnostic value, which is applicable also in places other than advanced centres, with low morbidity and mortality.
Keywords: lung cancer; lymphadenopathy; mediastinal staging; thoracic surgery